Platelet Count in Patients with Mild Disease at Admission is Associated with Progression to Severe Hantavirus Cardiopulmonary Syndrome - LOPEZ HERNANDEZ, RENE RAMON; Mario Calvo; VIAL COX, MARIA CECILIA; Marcela Ferrés; GRAF SANTOS, JERÓNIMO; Gregory Mertz; Analía Cuiza; Begonia Agüero; Dante Aguilera; Diego Araya; Ignacia Pailamilla; Flavia Paratori; et al. (My University, 2019)
Background: Hantavirus cardiopulmonary syndrome (HCPS) has a mortality up to 35–40% and its treatment is mainly supportive. A variable to predict progression from mild to severe disease is unavailable. This study was performed in patients with documented infection by Andes orthohantavirus, and the aim was to find a simple variable to predict progression to moderate/severe HCPS in patients with mild disease at admission. Methods: We performed a retrospective analysis of 175 patients between 2001 and 2018. Patients were categorized into mild, moderate, and severe disease according to organ failure and advanced support need at hospital admission (e.g., mechanical ventilation, vasopressors). Progression to moderate/severe disease was defined accordingly. Clinical and laboratory variables associated with progression were explored. Results: Forty patients with mild disease were identified; 14 of them progressed to moderate/severe disease. Only platelet count was different between those who progressed versus those that did not (37 (34–58) vs. 83 (64–177) K/mm3, p < 0.001). A ROC curve analysis showed an AUC = 0.889 (0.78–1.0) p < 0.001, with a platelet count greater than 115K /mm3 ruling out progression to moderate/severe disease. Conclusions: In patients with mild disease at presentation, platelet count could help to define priority of evacuation to tertiary care centers.
Keywords: hantavirus cardiopulmonary syndrome; hantavirus pulmonary syndrome; thrombocytopenia; adult; chile; disease progression; female; hantavirus infections; hantavirus pulmonary syndrome; humans; male; middle aged; platelet count; retrospective studies; roc curve; thrombocytopenia; young adult; alanine aminotransferase; aspartate aminotransferase; hypertensive factor; lactate dehydrogenase; adult; andes virus; area under the curve; arterial pressure; article; artificial ventilation; blood oxygen tension; cohort analysis; cross reaction; disease exacerbation; enzyme linked immunosorbent assay; female; hantavirus pulmonary syndrome; hospital admission; hospital mortality; hospitalization; human; interactive ventilatory support; length of stay; long term care; major clinical study; male; mortality rate; multiple organ failure; observational study; outcome assessment; platelet count; receiver operating characteristic; respiratory failure; retrospective study; reverse transcription polymerase chain reaction; blood; chile; classification; complication; disease exacerbation; hantavirus infection; hantavirus pulmonary syndrome; middle aged; platelet count; thrombocytopenia; virology; young adult